Math

posted by .

Which of the following is equal to log6(t + 1) − log6(t^2 − 1)?
A. log6t − log6t2
B. –log6(t − 1)
C. log6t
D. log6(t + 1)

  • Math -

    since (t+1)/(t^2-1) = 1/(t-1),

    (B)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra 2

    Can someone please explain to me how to solve logarithmic equations?
  2. Logs

    log6(x+7)−log6x=2 Solve for x
  3. Math

    log6(x+7)−log6x=2 Solve for x
  4. Math SAT Sheet

    1.) Find the domain and range for: f(x)= 4x-20/ the square root of 36-x^2 2.) Solve the equation: log6 (x-11) + log6 (x-6) = 2 3.) Solve the inequality: x^2 - 2x - 3 is greater than 0
  5. precalulus

    Ok feeling kinda dumb because this isn't coming out right. I know it's simple. log6 (x -3) + log6(x -6) - log6(x + 1) = 2
  6. biology

    Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner?
  7. Grade 12 Calculus

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  8. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  9. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  10. Math

    The problem I have to solve is log with base 2 ^6 multiply by log base 6 ^ 8. I use the change of base formula and got log6/log2 * log8/log6 Which become log6/log2 * log2()^3/ log 6 I'm stuck here thanks.

More Similar Questions